Acquired Thrombotic Thrombocytopenic Purpura and Atypical Hemolytic Uremic Syndrome Successfully Treated with Eculizumab. Issue 2 (1st April 2017) - Sasapu, Appalanaidu; Cottler-Fox, Michele; Motwani, Pooja
Abstract : Acquired idiopathic thrombotic thrombocytopenic purpura is a life-threatening disease with a mortality of up to 90%, if not promptly recognized and treated. We report a 64-year-old woman with this condition who presented with left-sided weakness and seizure-like activity preceded by headache and easy bruising. She did not achieve optimal response to plasma exchange, corticosteroids, rituximab, and vincristine. We initiated treatment with eculizumab, following which she had durable remission that continued for 30 months after discontinuation of the drug. We later found that our patient has homozygous deletion in two closely related genes, complement factor H–related 1 and complement factor H–related 3.